Réponses

Meilleure réponse !
2014-03-05T17:50:30+01:00
Bonjour

E = (2x+7)(2x-3)
4x² -6x +14x -21
= 4x² +8x -21

G = 2(2x+7) +2(2x-3)
4x +14 +4x -6
= 8x + 8

E représente l'aire de VOUS et G son périmètre

(2x+7) = 2(2x-3)
2x +7 = 4x - 6
2x -4x = -6 -7
-2x = -13
x = 6.5

si x = 6.5, G = 52 + 8 = 60
2014-03-05T18:05:30+01:00
Salut,

E = (2x+7)(2x-3)
4x² -6x +14x -21
= 4x² +8x -21

G = 2(2x+7) +2(2x-3)
4x +14 +4x -6
= 8x + 8



(2x+7) = 2(2x-3)
2x +7 = 4x - 6
2x -4x = -6 -7
-2x = -13
x = 6.5

si x = 6.5, G = 52 + 8 = 60